Analisis Daya Saing Ekspor Kakao Olahan Indonesia di Pasar Jerman: (The Analysis of Indonesian Processed Cocoa Export Competitiveness in The Market of Germany) - Ersalia Shifa Ramadhani; Ignatia Martha Hendrati; Kiki Asmara (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
One of the commodities which play a role in the economy of Indonesia is Cocoa, as one of the largest cocoa producers in the world, every year Indonesia keeps giving its effort to fulfilling the demand of the market, including Germany. This article has the objective of analyzing the competitiveness of Indonesian processed cocoa in Germany and analyzing the export competitiveness of processed cocoa between Indonesia and Ivory Coast, Belgium, Switzerland, and the Netherlands from 2014 to 2019. The data used are secondary data, obtained through various institutions such as the Indonesian National Agency for Statistics Center, International Trade Center (ITC), UN COMTRADE, and International Cocoa Organization (ICCO). In order to analyze the competitiveness of all processed cocoa commodities, the methodology used is Revealed Comparative Advantage (RCA). The result of the RCA calculation shows that all Indonesian processed cocoa commodities such as cocoa paste (HS 1803), cocoa butter (HS 1804), and cocoa powder (HS 1805) have a comparative advantage in the German market. The result of this analysis shows that cocoa powder commodity has a higher RCA score compared with the other processed cocoa products. The implication of the research is that the research was conducted as empirical support that cocoa processed commodities in Indonesia must be taken into account in order to compete in the German market. Indonesia must increase the export volume of its processed cocoa in order to increase the value of the domestic cocoa industry. This research is expected to provide input to the government so that it can provide assistance in the form of incentives to small cocoa entrepreneurs engaged in the export sector so that these entrepreneurs can reduce production costs and stabilize Indonesian cocoa prices.